2012
DOI: 10.1590/s0034-72802012000500005
|View full text |Cite
|
Sign up to set email alerts
|

Inflamação esclerosante idiopática da órbita: estudo clinico-patológico

Abstract: Trabalho realizado no Hospital Universitário Professor Edgard Santos, Universidade Federal da Bahia (UFBA) -Salvador (BA), Brasil RESUMOObjetivo: Descrever oito casos de inflamação esclerosante idiopática da órbita, incluindo a análise clínica e histopatológica. Métodos: Estudo retrospectivo através do livro de registros do Laboratório de Patologia Ocular (LPO) do Hospital Universitário Professor Edgard Santos, Universidade Federal da Bahia, no período de 1974 a 2010. Além de revisão de lâminas de todos os cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…It's a disease that corresponds to loss of parallelism between the eyes in a convergent, divergent or vertical way, can cause amblyopia of the deviated eye, affecting up to 5% of the world population. 20 Since eye alignment is a necessary condition for the normal development of vision and that such an aggravation needs to be detected and treated as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…It's a disease that corresponds to loss of parallelism between the eyes in a convergent, divergent or vertical way, can cause amblyopia of the deviated eye, affecting up to 5% of the world population. 20 Since eye alignment is a necessary condition for the normal development of vision and that such an aggravation needs to be detected and treated as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…It showed similar condition to the inflammatory pseudotumor, but more aggressive and with worse response to steroids (8) . The most common signs and symptoms observed are:proptosis (49%), orbital pain (12.2%), palpebral edema or mass (22.4%), diplopia (6.1%), visual loss (6.1%) and ptosis (4.1%) (11) .Another study also found pain, proptosis, palpebral edema, restriction of eye movements, ptosis and visual loss as the most common clinical condition (5) . The patient presented pain, edema and tumors of approximately one centimeter in the right eyelid, but he denied reduced visual acuity.…”
Section: Discussionmentioning
confidence: 96%
“…Sclerosing orbitalpseudotumor is a rare subtype of inflammatory orbital pseudotumor (5) . Its exact incidence is not described in the literature.It shows no significant difference of presentation in relation to gender, and the average age of patients is 44 years old (11) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations